DIFFERENT APPROACHES TO THE DEFINITION OF THE CONTENT OF THE CONCEPT "ACTIVE COMMUNICATIVE POSITION" IN SCIENTIFIC RESEARCH (Pedagogy of Higher and Secondary Education, 2022)
Various theoretical approaches to the definition of insight and the contents of the terms “active communicative position ” in scientific research are considered in the article. The author substantiated the necessity o f the form ation o f the pupils' active communicative position in the process o f studying.